2012 IEEE International Conference on Condition Monitoring and Diagnosis 2012
DOI: 10.1109/cmd.2012.6416297
|View full text |Cite
|
Sign up to set email alerts
|

The criteria of dissolved gas analysis in natural ester fluid

Abstract: In this paper, dissolved gasses of natural ester fluid were analyzed to suggest DGA criteria for transformer filled with natural ester fluid. Samples of mineral oil and natural ester fluid made to correspond to the ratios of the iron core, winding, insulating materials and insulating oil in a transformer were deteriorated for 1,600 hours in a 150 thermostat and samples were collected every two hundred hours to analyze changes in the contents of dissolved gases. As the results, H 2 and C 2 H 2 gases were hardly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In [57], five generated gases (H 2 , CH 4 , C 2 H 4 , C 2 H 6 , C 2 H 2 ) in mineral oil and natural ester under thermal stress with and without added transformer materials were compared. Both oils were deteriorated for 1600 h at 150°C and collected every 200 h to analyse changes in the contents of dissolved gases.…”
Section: General Differences Between Mineral Oil and Natural Estermentioning
confidence: 99%
“…In [57], five generated gases (H 2 , CH 4 , C 2 H 4 , C 2 H 6 , C 2 H 2 ) in mineral oil and natural ester under thermal stress with and without added transformer materials were compared. Both oils were deteriorated for 1600 h at 150°C and collected every 200 h to analyse changes in the contents of dissolved gases.…”
Section: General Differences Between Mineral Oil and Natural Estermentioning
confidence: 99%
“…It was reported that the condition (age) of the oil has a significant influence on the concentration of the dissolved gases which affects the fault diagnostic conditions. Also, the influence of thermal aging on the gassing tendency of mineral oil and natural esters under the influence of thermal faults has been reported in [19]. A significant change in the dissolved gas concentration has been noticed with an increase in the thermal aging duration of the dielectric fluids.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large amount of C 2 H 2 is generated as compared to the low energy discharge cases. The gassing tendency of ester fluids under thermal faulty condition was also investigated and are reported in [14,15,[18][19][20]. It is found that natural ester generates more gases at a higher temperature (>300 • C) and traces of C 2 H 6 are found increasing with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%